(3eNJUQ GdGcJaGQ aj GdbQBBJs - (3ESeGYjd Hf Nda GdfMhj GdebQj, CHh WGgQ,J (B455 (3g` s
(3ChdgG (B:s
(3bGd GdTjN CHh WGgQ GSeYjd CeG HYO aEfi CPcQ ai gPG GdcJGH Ef TGA Gddg JYGdi eG GNJda ajg GdbQGA GdSHYI GdeTghQhf ef GFeI GdCeUGQ s
(3BNQgG (B:s
(3cGf GdHRi EPG NJe ShQI (B" (3hGdVMi (B" (3cHQ Je GdcJGH HMeO Gddg hYhfg s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI YGQa MceJ HGdeOjfI GdefhQI(B((3bQBBJ (B53) s
Keywords: (3GdbQGAGJ hGdJLhjOs